Improvement of the Wald method applied to the evaluation of zero-inflated binomial linear functions - Peixoto, Cleide Silveira Brasil; Cirillo, Marcelo Angelo; Silva, Augusto Maciel da (Acta Scientiarum. Technology, 2015)
The Wald method is grounded on a statistic based on the asymptotic approximation of normal distribution. The method has shown incoherent values at a nominal level of confidence for the probability of coverage in intervallic estimates, mainly in small samples, noticeable in linear functions formed by binomial proportions. Current analysis improves this method used in inferring from binomial linear functions, taking into consideration zero-inflated samples. Improvement was assessed byMonte Carlosimulation techniques within different scenarios. Results show that the improvement proposed is recommended in situations in which sampling proportions are close to 0,5 and produce a maximum variance of the binomial proportions involved in the composition of the linear function. Â 